A Proposed Plan for Marketing Festivals and Sport Shows in the Light of the Anaslysis of the Reality in Syria - عجيب شيريهان; وائل معوض; خلود علي ديب (Latakia University Journal -Medical Sciences Series, 2023)
This Study aimes to suggest a new marketing plan for the sport shows that happens in Syria. The method that is used is the descriptive analytical, through interviews conducted by the researcher with 30 specialists in festivals and sport shows in Syria, to show the most appropriate ways to marketing festivals and sport shows, to make benefit from them bu an Economical point of view. The study concluded the importance of the marketing plan and the need of specialists for it to develop festivals in many respects, and it helps in financial support for festivals as it needs a lot of material and money support in the light of Economic poverty that the Country is experiencing at the present time. Keywords: sports shows, the components of the sports shows.